Percepce dopadů pandemie COVID-19 v Praze na sektor MICE - Chvátalová, Kateřina (Trendy v podnikání = Business trends, 2024)
The general public's perception of the period of the coronavirus pandemics in areas related to incoming tourism, business travel or the organisation of events has been influenced by the media. Although a strongly negative perception of this period in this field is to be expected, the author considered it necessary to conduct a detailed survey with the most experienced professionals in this field, with a certain distance that would allow to assess the situation without immediate strong emotions. More than a year after the end of the main anti-epidemic measures associated with the pandemic covid-19, the author conducted an addressed questionnaire survey with MICE professionals based in Prague (summer – autumn 2023). 110 professionals with many years of experience were targeted to determine the extent of the pandemic's impact on the MICE sector. From the 85 responses received, it was possible to define and describe interesting facts related to the perception of the affected sector by different professions and companies.